A method of corrosion of a superinvar alloy
Patent Information
- Application Number
- CN202511380683.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-25
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-09-25
AI Technical Summary
[0005]现有应用于超因瓦合金的金相腐蚀方案主要存在三类典型缺陷:其一,采用三氯化铁、盐酸与水按一定比例配制的腐蚀液时,腐蚀反应速率缓慢,且试样表面易形成大量疏松腐蚀产物,完全掩盖晶界与晶粒形态,无法实现任何有效的金相组织观察;其二,使用盐酸与硝酸的混合强酸体系时,因两种强酸反应活性剧烈,腐蚀时间极难精准控制,且溶液挥发性强,必须现配现用,不仅操作繁琐,还易导致晶界出现“浮突”现象(局部过度腐蚀易引发晶界边缘不规则凸起),晶界完整性与清晰度不足,频繁需重新磨制试样,大幅增加检测成本与耗时;其三,采用冰乙酸、浓硝酸与水的混合体系时,虽能一定程度降低腐蚀剧烈程度,但腐蚀时间仍需数分钟,且晶界显示不完整、对比度低,无法满足超因瓦合金晶粒度精确评级及相组成细节分析的科研与生产需求
①本发明所述方法采用180#→400#→800#→1200#梯次目数的打磨策略,逐步将表面划痕深度从数十微米降至≤0.5μm,每级砂纸磨粒粒径恰好覆盖前一级划痕深度,形成平整的磨制基底;同时结合“每换砂纸旋转90°”的操作,不仅便于通过交叉划痕方向直观判断前道划痕是否完全消除,还能避免单向受力导致的边缘薄化,彻底避免深划痕残留对后续抛光与腐蚀的干扰,使试样表面粗糙度Ra≤0.5μm、平面度误差≤0.01mm。
Smart Images

Figure CN121163995B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials microstructure detection technology, and specifically to a corrosion method for super Invar alloys. Background Technology
[0002] Metallographic testing is a core technology in materials science and engineering for analyzing the microstructure of materials. It reveals the grain morphology, grain boundary characteristics, phase composition, and defect distribution within the material, providing crucial information for material performance evaluation, production process optimization, and failure analysis. The corrosion effect of the metallographic sample directly determines the accuracy and reliability of metallographic testing and is a core step in the metallographic analysis process. The essence of metallographic corrosion is to utilize chemical or electrochemical action to selectively corrode different structures, grains, and grain boundaries on the material surface due to differences in electrochemical activity, thereby revealing a clear microstructure under a microscope. Its corrosion effect mainly depends on three core elements: the selection of etching solution components, the accuracy of the ratio, and the control of corrosion time. If the ratio of the etching solution is inappropriate, the sample may not reveal an effective metallographic structure or may be difficult to observe. If the corrosion time is too long, surface corrosion products accumulate, the metallographic surface turns dark black, and grain boundaries widen and become indistinguishable. If the corrosion time is too short, the grain boundaries of the metallographic structure are not obvious, neither of which can meet the requirements for accurate subsequent testing such as grain size rating and phase distribution analysis.
[0003] Super Invar alloy, a low-expansion iron-nickel-based functional alloy (its chemical composition is shown in Table 1), is increasingly widely used in high-end fields such as electronics, aerospace, marine, and nuclear industries due to its excellent low coefficient of expansion and mechanical properties. The stability of the alloy's microstructure at low temperatures and the presence of localized martensitic phase transformations significantly affect its expansion performance; therefore, precise control of its microstructure directly impacts the performance stability of end products. However, the complexity of the composition of super Invar alloy presents unique challenges for metallographic corrosion: based on iron and nickel, it contains multiple alloying elements such as cobalt, combining the localized corrosion intolerance of iron-based alloys with the overall corrosion resistance imparted by nickel. The significant differences in reactivity of different elements during corrosion make it difficult to achieve uniform and selective corrosion using conventional etching solutions, becoming a key bottleneck restricting its metallographic detection. Currently, technical data on the metallographic corrosion of super Invar alloy is extremely scarce. Most industry experiments refer to corrosion schemes for general iron-based alloys, but none have yielded ideal results.
[0004] Table 1: Chemical Element Content of Super Invar Alloy
[0005] Existing metallographic etching methods for super Invar alloys suffer from three main defects: First, when using an etching solution prepared with ferric chloride, hydrochloric acid, and water in a specific ratio, the corrosion reaction rate is slow, and a large number of loose corrosion products easily form on the sample surface, completely obscuring grain boundaries and grain morphology, making it impossible to observe any effective metallographic structure. Second, when using a mixed strong acid system of hydrochloric acid and nitric acid, the two strong acids react violently, making it extremely difficult to precisely control the etching time. Furthermore, the solution is highly volatile and must be prepared and used immediately, which is not only cumbersome but also easily leads to "floating protrusions" at grain boundaries (localized over-etching easily causes irregular protrusions at grain boundary edges), resulting in insufficient grain boundary integrity and clarity. Frequent sample re-grinding is required, significantly increasing testing costs and time. Third, while a mixed system of glacial acetic acid, concentrated nitric acid, and water can reduce the intensity of corrosion to some extent, the etching time still requires several minutes, and the grain boundary display is incomplete and has low contrast, failing to meet the research and production needs for accurate grain size rating and detailed phase composition analysis of super Invar alloys.
[0006] At the level of corrosion methods, traditional corrosion methods (including chemical corrosion and electrolytic corrosion) also have significant limitations, as follows: 1. Chemical corrosion method (taking the widely used immersion method as an example) Immersion method can easily leave corrosion residues on the sample surface, requiring an additional cleaning process; at the same time, the corrosion time is long and the effect is greatly affected by the uniformity of solution concentration, and the complex composition of Invar alloys makes it more prone to uneven local corrosion.
[0007] 2. Electrolytic corrosion method The electrolytic corrosion method requires precise control of multiple parameters such as electrolyte composition, electrolysis voltage, and current density, which makes the operation process complex and involves many variables. This not only results in low detection efficiency but also poor stability of the corrosion effect on super Invar alloys, making it difficult to adapt to batch testing or rapid analysis scenarios in production sites.
[0008] In conclusion, with the continued growth in demand for Super Invar alloys in high-end manufacturing, the industry urgently needs a metallographic etching solution and matching etching method that can adapt to the alloy's compositional characteristics, has excellent corrosion effects, is easy to operate, and is highly efficient, in order to solve the pain points of existing technologies and support the research and development innovation and production quality control of Super Invar alloy products. Summary of the Invention
[0009] The purpose of this invention is to solve the problems of the prior art and provide a corrosion method for super Invar alloys. Through standardized preparation of corrosion solution, sample pretreatment and corrosion operation, the corrosion solution is ensured to have good corrosion stability and accuracy for super Invar alloys. It can completely and clearly reveal the microstructure of the alloy. Moreover, the method is highly practical and easy to promote in industrialization, providing reliable morphological basis for microstructure analysis, production process optimization and scientific research of super Invar alloys.
[0010] The objective of this invention is achieved through the following approach: A method for etching super Invar alloys, comprising the following steps: 1) Preparation of etching solution: Nitric acid, glacial acetic acid and acetone are mixed evenly in a volume ratio of 6~7:4~5:0.8~1 to obtain etching solution; 2) Alloy sample preparation: The super Invar alloy to be tested is cut to obtain an alloy sample; 3) Mounting: The alloy sample is mounted to obtain a mounted sample; 4) Grinding: Grind the inlaid sample until the surface is smooth and flat to obtain the ground sample; 5) Polishing: Polish the ground sample with metallographic polishing paste until the observation surface of the sample is mirror-like, then clean the surface impurities and blow dry to obtain the polished sample; 6) Corrosion: Wipe the metallographic surface of the polished sample repeatedly with the etching solution for 20 seconds, then immediately clean the surface impurities and blow dry to obtain the etched sample.
[0011] Preferably, in step 1), the etchant is prepared by mixing nitric acid, glacial acetic acid, and acetone in a volume ratio of 6:4:1.
[0012] The preparation process of the etching solution in step 1) is as follows: Take 4-5 parts of glacial acetic acid and add it to 6-7 parts of nitric acid. After stirring and mixing thoroughly, take 0.8-1 parts of acetone and add it to the mixed solution of nitric acid and glacial acetic acid. After stirring and mixing thoroughly, let it stand for 1 minute to obtain the etching solution for metallographic etching of super Invar alloy.
[0013] The mass fraction of nitric acid mentioned in step 1) is 65%~68%, the mass fraction of glacial acetic acid is 99.5%, and the mass fraction of acetone is 99.5%.
[0014] The alloy sample mentioned in step 2) is the size suitable for metallographic testing.
[0015] The alloy sample size mentioned in step 2) is 10mm × 20mm.
[0016] Step 4) involves polishing the inlaid sample by sequentially using sandpaper with grits of 180#, 400#, 800#, and 1200#.
[0017] In step 4), when polishing the inlaid sample with sandpaper, rotate the sample 90° each time you change the sandpaper until the scratches caused by the previous sandpaper are completely gone.
[0018] The particle size of the metallographic polishing paste mentioned in step 5) is W2.5μm.
[0019] The advantages of this invention are as follows: ① The method described in this invention adopts a grinding strategy of 180#→400#→800#→1200# grit size, gradually reducing the surface scratch depth from tens of micrometers to ≤0.5μm. The abrasive grain size of each grade of sandpaper exactly covers the scratch depth of the previous grade, forming a flat grinding base. At the same time, combined with the operation of "rotating 90° every time the sandpaper is changed", it is not only convenient to intuitively judge whether the previous scratch has been completely eliminated by the cross scratch direction, but also avoids edge thinning caused by unidirectional force, and completely avoids the interference of deep scratch residue on subsequent polishing and corrosion, so that the surface roughness Ra of the sample is ≤0.5μm and the flatness error is ≤0.01mm.
[0020] ② This invention employs a precise etching time of 20 seconds and the operation of "repeated wiping + immediate cleaning and drying" to ensure clear contrast of metallographic structure without secondary etching damage. The microstructure detail visibility rate reaches over 98%, thoroughly removing polishing wax and grinding debris. This solves the problem of uneven grinding caused by the single grinding direction in traditional methods, and avoids interference from "false structures" formed by incomplete cleaning, providing high-quality samples with consistent surface conditions for subsequent etching processes.
[0021] ③ This invention is simple to operate and significantly improves corrosion efficiency. The corrosion solution configuration parameters of this invention are clear, the operation is simple, and the corrosion method steps are clear and easy to master. At the same time, using the corrosion method of this invention, the corrosion process can be completed in only 20 seconds, compared with about 30 minutes in the prior art. The corrosion process is greatly shortened, significantly improving the detection efficiency and effectively adapting to the pace requirements of batch testing and large-scale production.
[0022] ④ The metallographic etching solution for super Invar alloys prepared by this invention exhibits excellent etching performance, clearly and completely revealing the microstructure of super Invar alloys. Even for super Invar alloys in different states (such as annealed and cold-rolled states), the metallographic etching solution of this invention achieves excellent etching results, clearly and completely displaying the austenitic grain boundaries, with complete grain morphology, clear grain boundary outlines, and virtually no corrosion product residue within the grains. Combined with a metallographic microscope, it can clearly distinguish the various phase compositions of the alloy's metallographic structure, accurately assess the grain size level, and provide reliable morphological basis for the microstructure analysis of super Invar alloys.
[0023] ⑤ This invention has a wide range of applications and high practical value. The glacial acetic acid, nitric acid, and acetone used in this invention are all conventional chemical raw materials. Acetone is used in small quantities and accounts for a low percentage of the cost, making it highly practical and easy to promote industrially. It is not only suitable for mass production and large-scale application, but also supports manufacturing enterprises in developing new products and optimizing production process parameters, as well as research institutions in conducting research on the microstructure of materials, thus possessing extremely high practical application value. Attached Figure Description
[0024] Figure 1 This is a flowchart of the corrosion method for the super Invar alloy in this invention; Figure 2 The image shows the microstructure of the super Invar alloy sample in Example 1. Figure 3 for Figure 2 Magnified image of the microstructure morphology of the Invar alloy sample from the Chinese Super League; Figure 4 The image shows the microstructure of the super Invar alloy sample in Example 2. Figure 5 The image shows the microstructure of the super Invar alloy sample in Example 3. Figure 6 The image shows the microstructure of the super Invar alloy sample in Comparative Example 1. Figure 7 The image shows the microstructure of the super Invar alloy sample in Comparative Example 2. Detailed Implementation
[0025] like Figures 1 to 2 As shown, a method for etching super Invar alloys includes the following steps: 1) Preparation of corrosive solution 1-1) Prepare raw materials 1-1-1) Nitric acid with a mass fraction of 65%~68% provides stable oxidative corrosion resistance to the corrosive solution; 1-1-2) Glacial acetic acid with a mass fraction of 99.5%: provides precise acidity adjustment for the corrosive solution; 1-1-3) Acetone with a mass fraction of 99.5%: The etching solution provides a highly efficient surface cleaning effect.
[0026] 1-2) Preparation process First, add 4-5 parts by volume of glacial acetic acid to 6-7 parts by volume of nitric acid and stir thoroughly until the mixture is homogeneous. Then, add 0.8-1 parts by volume of acetone to the mixture of nitric acid and glacial acetic acid and continue stirring thoroughly until the mixture is homogeneous. Finally, cover the container and let it stand for 1 minute to obtain an etching solution that can be used for metallographic etching of Invar alloys.
[0027] In this etching solution, nitric acid can specifically remove the oxide layer formed on the surface of the Invar alloy due to processing or storage, and selectively corrode the matrix phase and second-phase particles of the alloy matrix, creating a clear contrast between the phases and laying the foundation for the manifestation of metallographic features. Glacial acetic acid precisely controls the excessive oxidizing activity of nitric acid by adjusting the pH value in the etching solution system. This avoids problems such as excessively fast corrosion rate due to excessively high nitric acid content, which could lead to blurred grain boundaries and dissolution of second-phase particles. It also prevents problems such as excessively slow corrosion rate due to excessively low nitric acid content or excessively high glacial acetic acid content, which could lead to insufficient exposure of microstructure features. Acetone can quickly dissolve residual grease (such as cutting fluid residue from processing) and polishing paste wax components on the sample surface, and remove surface-attached wear debris and impurities. This avoids the problem of incomplete impurity removal due to excessively low acetone content, which could form an "isolation layer" affecting the full contact between the etching solution and the alloy matrix, and also avoids the problem of excessively high acetone content diluting the effective concentration of nitric acid in the etching solution, which could reduce the corrosion efficiency. This further ensures the uniformity of corrosion.
[0028] The preferred method for preparing the above-mentioned etching solution is as follows: Nitric acid, glacial acetic acid, and acetone of the above specifications are mixed in a volume ratio of 6:4:1, following the same mixing sequence and standing steps as described above. After mixing thoroughly and standing for 1 minute, a superior metallographic etching solution for Super Invar alloys is obtained. Using this ratio can significantly reduce the etching deviation of samples from the same batch, greatly improve the clarity of microstructure visualization, effectively reduce observation errors, and fully ensure the stability and accuracy of the metallographic etching effect on Super Invar alloys.
[0029] 2) Alloy sample preparation The super Invar alloy to be tested is cut into 10mm×20mm or a size suitable for metallographic testing using a cutting machine to obtain alloy samples.
[0030] 2-1) The alloy sample is 10mm × 20mm in size. Cutting the Super Invar alloy into a specific size of 10mm × 20mm fully meets the size specifications for test specimens in GB / T6394-2017 "Method for Determination of Average Grain Size of Metals". It also closely matches the cavity size of existing conventional metallographic mounting molds, ensuring stable fixation of the specimen at the mold center during mounting. This avoids problems such as specimen displacement and uneven embedding material due to dimensional deviations, thus preventing defects such as over-processing of edges or unadjustment of the center during subsequent grinding and polishing. Furthermore, the 10mm × 20mm observation surface area fully covers the field of view requirements of mainstream metallographic microscopes, allowing for the capture of a sufficiently large microstructure area during testing. This facilitates the analysis of the overall microstructure distribution and representative characteristics of the Super Invar alloy, improving the accuracy and comprehensiveness of the test results. Moreover, the specimen weight is kept within a reasonable range at this size, maintaining stability during processing, whether by hand or with a clamp, significantly reducing the risk of specimen bumps and scratches caused by operational imbalances.
[0031] 2-2) The alloy sample is sized to be suitable for metallographic testing. Cutting the super Invar alloy to a size suitable for metallographic inspection is based on precise considerations of actual inspection scenarios. When using special-type metallographic microscopes or when focusing on minute defects, the sample size can be adjusted to suitable dimensions such as 5mm×10mm or 8mm×8mm. This not only meets the stage specifications of the equipment but also allows for focusing on the target inspection area by reducing the observation surface, avoiding interference from irrelevant areas. This flexible design allows the invention to be adapted to different inspection equipment and inspection needs, breaking the limitation of a single size on application scenarios.
[0032] 3) Inlay The alloy sample is integrally mounted using a metallographic mounting machine to obtain a mounted sample. This type of mounted sample ensures uniform stress during subsequent grinding and polishing, effectively avoiding problems such as deformation and edge warping caused by the lack of fixed support for the alloy sample, and ensuring the flatness of the sample observation surface.
[0033] 4) Polishing The surface of the mounted specimen to be corroded was successively polished using sandpaper with grits of 180#, 400#, 800#, and 1200#, gradually reducing the size of the polishing scratches and effectively eliminating surface damage caused during the rough polishing stage. Simultaneously, during the polishing process, the specimen was rotated 90° each time the sandpaper was changed, ensuring the new polishing direction was perpendicular to the scratches from the previous sandpaper pass. This precisely exposed the old scratches, facilitating their removal by the operator, until the scratches from the previous sandpaper pass were completely eliminated, ensuring a smooth and flat surface for the polished specimen.
[0034] Among them, the abrasive grain size and hardness of 180# sandpaper are matched with the physical properties of Invar alloy (low coefficient of expansion, certain hardness), which can efficiently remove deep scratches, edge burrs and irregular protrusions on the surface of the inlaid sample caused by the previous cutting and inlaying process. It can quickly remove cutting marks on the sample surface and preliminarily trim the shape of the sample. 400# sandpaper can accurately eliminate the coarse grinding marks left by 180# paper, greatly reduce the surface roughness of the sample, and further reduce the depth of surface scratches. 800# sandpaper can further refine the surface and ensure that the surface flatness continues to improve. 1200# sandpaper has an extremely small abrasive grain size, which can perform final fine treatment on the sample surface. While maintaining flatness, it can minimize the "micro scratch clusters" that are easily generated by high-grit sandpaper grinding, and finally reduce the surface scratch depth to ≤1μm.
[0035] 5) Polishing On a polishing machine, a metallographic polishing paste with a particle size of W2.5μm was used to polish the ground sample. This particle size polishing paste is characterized by its fine and uniform particle size distribution, which can accurately adapt to the microstructure of the ground sample surface, efficiently remove the oxide layer and grinding impurities on the ground sample surface, and minimize disturbance to the microstructure of the super Invar alloy matrix. Polishing was carried out until the observation surface of the ground sample was mirror-like to thoroughly remove the grinding debris, polishing paste particles and micro-scratches remaining on the surface. Subsequently, the surface was wiped with degreased cotton, residual impurities were rinsed with alcohol, and then dried to obtain the polished sample.
[0036] 6) Corrosion Wipe the metallographic surface of the polished sample repeatedly with degreased cotton soaked in etching solution for 20 seconds. This ensures that the etching solution is in full contact with the metallographic surface of the sample, ensuring uniform etching and precise control of the etching degree. It also prevents the grain boundaries or second phase of the microstructure from being unclear due to excessive etching time, which would make it impossible to complete the subsequent microstructure evaluation work.
[0037] Immediately after wiping, rinse the sample surface with alcohol and blow dry to avoid the residual corrosion liquid from continuing to act on the sample surface and to prevent the already revealed metallographic structure from being damaged by secondary corrosion. This ensures that the details of the metallographic structure, such as the grain morphology, grain boundary characteristics, and second phase distribution of the super Invar alloy, are fully and clearly presented, and finally a corrosion sample suitable for metallographic observation is obtained.
[0038] 7) Metallographic structure observation The metallographic structure of the corroded sample was observed using a metallographic microscope to complete the analysis of the metallographic structure of the super Invar alloy.
[0039] Finally, when observing the corroded samples using a metallographic microscope, clear and accurate metallographic images of the super Invar alloy can be obtained, enabling precise analysis of key indicators such as grain size, microstructure uniformity, and the size and distribution of second-phase particles. These observation results provide reliable technical support for the performance analysis, quality inspection, and subsequent process optimization of super Invar alloys, meeting the practical needs of industrial production for quality control and performance optimization of super Invar alloys.
[0040] The following is an example of the etching method using the above-described Invar alloy metallographic etching solution: Example 1
[0041] A method for etching super Invar alloys using a metallographic etching solution includes the following steps: First, measure 60 mL of 65% nitric acid and pour it into a beaker; then measure 40 mL of 99.5% glacial acetic acid and pour it into the beaker; finally, measure 10 mL of 99.5% acetone and pour it into the beaker; stir with a glass rod to mix the components evenly, then cover and let stand for 1 minute to obtain the Super Invar alloy metallographic etching solution (referred to as Example 1 - Super Invar alloy metallographic etching solution).
[0042] The super Invar alloy to be tested was cut into 10mm×20mm pieces using a cutting machine to obtain alloy samples. The alloy samples were then mounted using a metallographic mounting machine to obtain mounted samples. The mounted samples were then ground sequentially with sandpaper of grits 180#, 400#, 800#, and 1200# until the surface of the mounted samples was smooth and flat to obtain ground samples. During the grinding process of the mounted samples, the samples were rotated 90° for grinding each time the sandpaper was changed until the scratches caused by the previous sandpaper were completely gone.
[0043] On a polishing machine, the grinding sample is polished with metallographic polishing paste with a particle size of W2.5μm until the observation surface of the grinding sample has a mirror effect. Then, the sample surface is wiped with degreased cotton, residual impurities in the sample are rinsed with alcohol, and the sample is dried to obtain a polished sample.
[0044] The surface of the polished sample was repeatedly wiped with the metallographic etching solution of Example 1-Super Invar alloy using degreased cotton. After wiping for 20 seconds, the sample surface was immediately cleaned with alcohol, then cleaned again with running water, sprayed with alcohol, and dried with a hair dryer to obtain the etched sample. The metallographic structure of the etched sample was observed using a metallographic microscope to complete the systematic analysis of the metallographic structure of Super Invar alloy.
[0045] from Figure 3 , Figure 4As can be seen, the etching solution prepared in Example 1 of this invention for etching the super Invar alloy sample can produce excellent etching effect: the grain morphology is fully presented, the grain boundary outline is clearly distinguishable, and the distribution of each phase, as well as the details of the structure such as precipitates and inclusions, are accurately revealed.
[0046] From a scientific research perspective, this corrosion effect provides reliable microscopic morphological evidence for the analysis of material microstructure, the study of phase transformation laws, and the exploration of the correlation between processes, microstructure, and properties. It helps researchers accurately grasp the essential characteristics of materials and lays a solid experimental foundation for the development of new materials and the optimization of processes. From a production perspective, it can effectively support quality monitoring and process verification, making it easier for technicians to quickly determine the rationality of material preparation processes, identify and solve microstructural defects in a timely manner, and ensure the stability of product quality. At the same time, it provides intuitive microstructural evaluation standards for the standardization and normalization of production processes, achieving synergistic improvement between scientific research and production. Example 2
[0047] A method for etching super Invar alloys using a metallographic etching solution includes the following steps: First, measure 65 mL of 65% nitric acid and pour it into a beaker; then measure 45 mL of 99.5% glacial acetic acid and pour it into the beaker; then measure 9 mL of 99.5% acetone and pour it into the beaker; stir with a glass rod to mix the components evenly, then cover and let stand for 1 minute to obtain the Super Invar alloy metallographic etching solution (referred to as Example 2 - Super Invar alloy metallographic etching solution).
[0048] The super Invar alloy to be tested was cut into 10mm×20mm pieces using a cutting machine to obtain alloy samples. The alloy samples were then mounted using a metallographic mounting machine to obtain mounted samples. The mounted samples were then ground sequentially with sandpaper of grits 180#, 400#, 800#, and 1200# until the surface of the mounted samples was smooth and flat to obtain ground samples. During the grinding process of the mounted samples, the samples were rotated 90° for grinding each time the sandpaper was changed until the scratches caused by the previous sandpaper were completely gone.
[0049] On a polishing machine, the grinding sample is polished with metallographic polishing paste with a particle size of W2.5μm until the observation surface of the grinding sample has a mirror effect. Then, the sample surface is wiped with degreased cotton, residual impurities in the sample are rinsed with alcohol, and the sample is dried to obtain a polished sample.
[0050] The surface of the polished sample was repeatedly wiped with degreased cotton soaked in the metallographic etching solution of Example 2 - Super Invar alloy. After wiping for 20 seconds, the sample surface was immediately cleaned with alcohol, then cleaned again with running water, sprayed with alcohol, and dried with a hair dryer to obtain the etched sample. The metallographic structure of the etched sample was observed using a metallographic microscope to complete the systematic analysis of the metallographic structure of Super Invar alloy.
[0051] from Figure 5 As can be seen, the metallographic etching solution for super Invar alloy prepared in Example 2 of this invention, after etching the super Invar alloy sample, can produce a good etching effect on the super Invar alloy metallographic structure: the grain morphology is complete, the grain boundary outline is clear, and the distribution of each phase and the details of the structure are accurately revealed. Based on this etching effect, the metallographic structure of the alloy can be accurately observed through a metallographic microscope, and the grain size can be evaluated and measured. Example 3
[0052] A method for etching super Invar alloys using a metallographic etching solution includes the following steps: First, measure 70 mL of 65% nitric acid and pour it into a beaker; then measure 50 mL of 99.5% glacial acetic acid and pour it into the beaker; then measure 8 mL of 99.5% acetone and pour it into the beaker; stir with a glass rod to mix the components evenly, then cover and let stand for 1 minute to obtain the Super Invar alloy metallographic etching solution (referred to as Example 3 - Super Invar alloy metallographic etching solution).
[0053] The super Invar alloy to be tested was cut into 10mm×20mm pieces using a cutting machine to obtain alloy samples. The alloy samples were then mounted using a metallographic mounting machine to obtain mounted samples. The mounted samples were then ground sequentially with sandpaper of grits 180#, 400#, 800#, and 1200# until the surface of the mounted samples was smooth and flat to obtain ground samples. During the grinding process of the mounted samples, the samples were rotated 90° for grinding each time the sandpaper was changed until the scratches caused by the previous sandpaper were completely gone.
[0054] On a polishing machine, the grinding sample is polished with metallographic polishing paste with a particle size of W2.5μm until the observation surface of the grinding sample has a mirror effect. Then, the sample surface is wiped with degreased cotton, residual impurities in the sample are rinsed with alcohol, and the sample is dried to obtain a polished sample.
[0055] The surface of the polished sample was repeatedly wiped with the metallographic etching solution of the Super Invar alloy prepared in Example 3 using degreased cotton. After wiping for 20 seconds, the sample surface was immediately cleaned with alcohol, then cleaned again with running water, sprayed with alcohol, and dried with a hair dryer to obtain the etched sample. The metallographic structure of the etched sample was observed using a metallographic microscope to complete the systematic analysis of the metallographic structure of the Super Invar alloy.
[0056] from Figure 6 As can be seen, the etching solution for ultra-Invar alloys prepared in Example 3 of this invention, after etching the ultra-Invar alloy sample, produces excellent etching results: the grain morphology is fully exposed, the grain boundary contours are clearly distinguishable, and the distribution of each phase and the details of the structure (such as precipitates, micro-inclusions, etc.) are accurately presented. Based on this etching effect, the metallographic structure of ultra-Invar alloys can be accurately observed using a metallographic microscope, and grain size assessment and measurement can be effectively carried out, providing reliable morphological basis for subsequent material microscopic analysis and quality control.
[0057] Comparative Example 1 A method for etching super Invar alloys using a metallographic etching solution includes the following steps: First, measure 60 mL of 36% concentrated hydrochloric acid and pour it into a beaker; then measure 20 mL of 65% nitric acid and pour it into the beaker; stir with a glass rod to mix the components evenly, cover and let stand for 5 minutes to obtain the super Invar alloy metallographic etching solution (referred to as Comparative Example 1 - Aqua regia system super Invar alloy metallographic etching solution).
[0058] The super Invar alloy to be tested was cut into 10mm×20mm pieces using a cutting machine to obtain alloy samples. The alloy samples were then mounted using a metallographic mounting machine to obtain mounted samples. The mounted samples were then ground sequentially with sandpaper of grits 180#, 400#, 800#, and 1200# until the surface of the mounted samples was smooth and flat to obtain ground samples. During the grinding process of the mounted samples, the samples were rotated 90° for grinding each time the sandpaper was changed until the scratches caused by the previous sandpaper were completely gone.
[0059] On a polishing machine, the grinding sample is polished with metallographic polishing paste with a particle size of W2.5μm until the observation surface of the grinding sample has a mirror effect. Then, the sample surface is wiped with degreased cotton, residual impurities in the sample are rinsed with alcohol, and the sample is dried to obtain a polished sample.
[0060] The surface of the polished sample was repeatedly wiped with degreased cotton soaked in the metallographic etching solution of the comparative example 1-aqua regia system for super Invar alloy. After wiping for 1 minute, the sample surface was immediately cleaned with alcohol, then cleaned again with running water, sprayed with alcohol, and dried with a hair dryer to obtain the etched sample. The metallographic structure of the etched sample was observed using a metallographic microscope to complete the systematic analysis of the metallographic structure of super Invar alloy.
[0061] from Figure 6 It is evident that the metallographic structure of the super Invar alloy sample was poorly presented after etching with the super Invar alloy metallographic etching solution of Comparative Example 1-Aqua regia system: some grain boundaries were displayed in a step-like manner, while some grain boundaries were not visible, resulting in incomplete and unclear grain boundary display on the metallographic surface; moreover, residual etching products on the surface not only hindered the observation of metallographic details but also directly affected the grain size rating work.
[0062] Comparative Example 2 A method for etching super Invar alloys using a metallographic etching solution includes the following steps: First, measure 60 mL of 99.5% glacial acetic acid and pour it into a beaker; then measure 40 mL of 65% nitric acid and pour it into the beaker; finally, measure 10 mL of distilled water and pour it into the beaker; stir with a glass rod to mix the components evenly, cover and let stand for 1 minute to obtain the super Invar alloy metallographic etching solution (referred to as Comparative Example 2 - Glacial Acetic Acid-Nitric Acid-Water System Super Invar Alloy Metallographic Etching Solution).
[0063] The super Invar alloy to be tested was cut into 10mm×20mm pieces using a cutting machine to obtain alloy samples. The alloy samples were then mounted using a metallographic mounting machine to obtain mounted samples. The mounted samples were then ground sequentially with sandpaper of grits 180#, 400#, 800#, and 1200# until the surface of the mounted samples was smooth and flat to obtain ground samples. During the grinding process of the mounted samples, the samples were rotated 90° for grinding each time the sandpaper was changed until the scratches caused by the previous sandpaper were completely gone.
[0064] On a polishing machine, the grinding sample is polished with metallographic polishing paste with a particle size of W2.5μm until the observation surface of the grinding sample has a mirror effect. Then, the sample surface is wiped with degreased cotton, residual impurities in the sample are rinsed with alcohol, and the sample is dried to obtain a polished sample.
[0065] Using degreased cotton soaked in the comparative example 2-glacial acetic acid-nitric acid-water system of the super Invar alloy metallographic etching solution, the surface of the polished sample was repeatedly wiped. After wiping for 2 minutes, the sample surface was immediately cleaned with alcohol, then cleaned again with running water, sprayed with alcohol, and dried with a hair dryer to obtain the etched sample. The metallographic structure of the etched sample was observed using a metallographic microscope to complete the systematic analysis of the metallographic structure of the super Invar alloy.
[0066] from Figure 7 It is evident that using the comparative example 2-glacial acetic acid-nitric acid-water system for etching the polished sample of Super Invar alloy resulted in unsatisfactory metallographic microstructure: some grain boundaries were not visible, leading to incomplete grain boundary display on the entire metallographic observation surface, and the clarity of the visible grain boundaries was insufficient; at the same time, details of the metallographic microstructure (such as precipitates, micro-inclusions, etc.) could not be effectively observed. These defects directly resulted in difficulties in carrying out grain size rating work normally, and could not provide reliable microstructure morphology basis for the microscopic analysis and quality control of Super Invar alloy.
[0067] In summary, for the metallographic etching requirements of Super Invar alloys, the commonly used etching solutions in the existing technology (such as aqua regia, glacial acetic acid-nitric acid-water mixed solutions, etc.) have obvious technical defects. Specifically, after etching Super Invar alloys with the above-mentioned existing etching solutions, the grain boundaries of the alloy structure are not obvious and the clarity is insufficient. This cannot meet the technical requirements for accurate observation of the metallographic structure and grain size rating of Super Invar alloys, and it is difficult to support subsequent material microscopic analysis and quality control.
[0068] The Super Invar alloy metallographic etching solution provided by this invention (with glacial acetic acid, nitric acid, and acetone as core components) introduces acetone into the glacial acetic acid-nitric acid system and ensures thorough mixing of all components. Acetone plays a crucial role in effectively promoting complete and uniform etching of the Super Invar alloy metallographic surface, resulting in excellent etching performance: intact grain morphology and clean, clear grain boundaries, meeting the requirements for precise observation of the alloy metallographic structure. Furthermore, the etching solution described in this invention has a simple preparation process, and the accompanying etching method is convenient to operate and has a short etching time (only 20 seconds). This not only effectively solves the technical problem of poor etching performance of Super Invar alloys but also significantly improves etching efficiency.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications made to the present invention by those skilled in the art without departing from the spirit of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for etching super Invar alloys, characterized in that, Includes the following steps: 1) Preparation of etching solution: Mix 65%~68% nitric acid, 99.5% glacial acetic acid, and 99.5% acetone in a volume ratio of 6~7:4~5:0.8~1 to obtain the etching solution; 2) Alloy sample preparation: The super Invar alloy to be tested is cut to obtain an alloy sample; 3) Mounting: The alloy sample is mounted to obtain a mounted sample; 4) Grinding: The inlaid sample is ground with sandpaper of grits of 180#, 400#, 800# and 1200# in sequence until the surface is smooth and flat, thus obtaining the ground sample; 5) Polishing: Polish the ground sample with metallographic polishing paste until the observation surface of the sample is mirror-like, then clean the surface impurities and blow dry to obtain the polished sample; 6) Corrosion: Wipe the metallographic surface of the polished sample repeatedly with the etching solution for 20 seconds, then immediately clean the surface impurities and blow dry to obtain the etched sample.
2. The corrosion method for super Invar alloy according to claim 1, characterized in that, In step 1), the etchant is prepared by mixing nitric acid, glacial acetic acid, and acetone in a volume ratio of 6:4:
1.
3. The corrosion method for super Invar alloy according to claim 1 or 2, characterized in that, The preparation process of the etching solution in step 1) is as follows: Take 4-5 parts of glacial acetic acid and add it to 6-7 parts of nitric acid. After stirring and mixing thoroughly, take 0.8-1 parts of acetone and add it to the mixed solution of nitric acid and glacial acetic acid. After stirring and mixing thoroughly, let it stand for 1 minute to obtain the etching solution for metallographic etching of super Invar alloy.
4. The corrosion method for super Invar alloy according to claim 1 or 2, characterized in that, The alloy sample mentioned in step 2) is the size suitable for metallographic testing.
5. The corrosion method for super Invar alloy according to claim 1 or 2, characterized in that, The alloy sample size mentioned in step 2) is 10mm × 20mm.
6. The corrosion method for super Invar alloy according to claim 1 or 2, characterized in that, In step 4), when polishing the inlaid sample with sandpaper, rotate the sample 90° each time you change the sandpaper until the scratches caused by the previous sandpaper are completely gone.
7. The corrosion method for super Invar alloy according to claim 1 or 2, characterized in that, The particle size of the metallographic polishing paste mentioned in step 5) is W2.5μm.
Citation Information
Patent Citations
Metallographic etching agent
CN101104935A
Magnesium alloy metallographic corrosive agent and preparation method and application thereof
CN118726979A